2019
DOI: 10.1523/eneuro.0141-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Resurgent and Gating Pore Currents Induced byDe Novo SCN2AEpilepsy Mutations

Abstract: Over 150 mutations in the SCN2A gene, which encodes the neuronal Nav1.2 protein, have been implicated in human epilepsy cases. Of these, R1882Q and R853Q are two of the most commonly reported mutations. This study utilized voltage-clamp electrophysiology to characterize the biophysical effects of the R1882Q and R853Q mutations on the hNav1.2 channel, including their effects on resurgent current and gating pore current, which are not typically investigated in the study of Nav1.2 channel mutations. HEK cells tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 73 publications
6
48
1
Order By: Relevance
“…For example, patients with epilepsy that is driven by SCN2A mutations that enhance persistent and/or resurgent current, such as the R1882Q mutation, may benefit from this compound. This mutation depolarizes the voltage dependence of inactivation, slows inactivation, and enhances both persistent and resurgent currents [12]. CBD will likely selectively inhibit the aberrantly enhanced resurgent currents in this mutant form of the hNav1.2 channel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, patients with epilepsy that is driven by SCN2A mutations that enhance persistent and/or resurgent current, such as the R1882Q mutation, may benefit from this compound. This mutation depolarizes the voltage dependence of inactivation, slows inactivation, and enhances both persistent and resurgent currents [12]. CBD will likely selectively inhibit the aberrantly enhanced resurgent currents in this mutant form of the hNav1.2 channel.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of resurgent currents in the pathogenicity of epilepsy mutations of SCN2A has only recently begun to be investigated. Though there is not yet evidence that the enhancement of resurgent current is a primary pathogenic mechanism of SCN2A epilepsy mutations, one recent study [12] showed that enhancement of Nav1.2-mediated resurgent currents was among the effects of the R1882Q mutation, which has been reported as likely pathogenic in many epilepsy patients, and which was predicted by Berecki et al [46] to enhance neuronal excitability. Kearney et al [47] demonstrated that a mutation that enhances Nav1.2 persistent currents in mouse neurons induces seizures and a strong epileptic phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Heron et al, 2002;Scalmani et al, 2006;Misra et al, 2008) L1563V DIV Missense BFNIS Increase in neuronal excitability Accelerated recovery from fast inactivation (Heron et al, 2002;Scalmani et al, 2006;Xu et al, 2007;Misra et al, 2008;Berecki et al, Epileptic seizure with pale, atonic periods followed by a spasm-like out-throwing of both arms Predominantly right-sided epileptiform activity (EEG) (Davidsson et al, 2008) *Non genetic origin mutations reported: Mutations described through clinical diagnosis, but the mutation type (Mendelian or de novo) were not reported, mainly due to the lack of parents to perform genotyping and difficulty in contacting the family. Normally, LoF SCN2A gene mutations for epilepsy are related to late-onset epilepsy; however, the mechanism of action is unclear (Mason et al, 2019). In some cases, NaV1.2 seizures are not controlled not even by various antiepileptic drugs, as with the patient described by Syrbe and colleagues (2016).…”
Section: Referencementioning
confidence: 99%
“…These experiments were motivated by a prior report indicating that the epilepsy-associated mutation SCN2A-R1882Q affecting a nearby residue had greater resurgent current than WT channels. 14 We recorded resurgent current in WT and M1879T expressing cells elicited by the voltage protocol shown in Figure 3A This difference was evident across several tested voltages with comparisons made using either current density (Figure 3B) or the level of resurgent current measured as a percentage of the peak current elicited at -10 mV (Figure 3C). Enhanced resurgent current exhibited by M1879T channels may contribute to the gain of sodium conductance conferred by this mutation.…”
Section: M1879t Channels Exhibit Enhanced Resurgent Currentmentioning
confidence: 94%